Performance decrease following summer break in youth swimmers - Zinner, C.; Sperlich, B.; Krueger, M.; Mester, J. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: Children in Germany have 6 weeks of school break. During this time usually no swim training is performed leading to a decrease in performance which was built up before the school break. The aim of the study was to evaluate the amount of performance loss following 6 weeks of summer break in youth swimmers. METHODS: 26 competitive swimmers between 9 and 11 years (MW 11.5 ± 1.4 yrs) participated in the study. Seven weeks before the summer break the kids performed a 100m all-out swim and a 2000m all-out swim. After five weeks of training the two tests were performed again. After the second test day the summer break occurred (6 weeks) without any swim specific training. Two and eight weeks after the summer break the tests were repeated again. RESULTS: The swimmers achieved a time of 35:31.2 ± 5:14.5min (2000m) and 1:25.4 ± 0:10.8 min (100m) during the first tests. After five weeks of training the times decreased without tatistical significance (2000m 34:52.8 ± 4:35.0 min; 100m 1:24.3 ± 0:10.4min). Two weeks after the summer break the performance level in both tests decreased significantly (2000m 36:11.6 ± 5:01.4 min; 100m 1:26.7 ± 0:09.7min). After a short period of training, the performance increased significantly and the swimmers nearly reached their level of the time before the summer break (2000m 35:10.7 ± 4:34.4 min; 100m 1:24.3 ± 0:10.3min). DISCUSSION: We could show that junior swimmers between 9 and 11 years of age are able to rebuild their performance level in six weeks of training. Therefore the summer break of six weeks is very important in competitive junior swimming. From a physiological and psychological point of view, young athletes need a break from daily training to regenerate and motivate again for the next season.